Dimensions of music use motivations: Genetic and environmental underpinnings, and associations with Big Five and Empathy traits - Heidi Marie Umbach Hansen; Espen Røysamb; Olav Mandt Vassend; Nikolai Olavi Czajkowski; Tor Endestad; Jonna Katariina Vuoskoski; Anne Danielsen; Bruno Laeng (PLoS ONE, 2025)
People differ in their motivation for seeking musical experiences and these differences appear to be partially attributable to their personality. However, little is known about the role of genetic and environmental factors in shaping individual differences in motivations for music use and their shared etiology with personality. This study investigated, using the classical twin design in a sample of 2611 Norwegian twins, the genetic and environmental architecture of four dimensions of motivations for music use (musical transcendence, emotion regulation, social bonding, and musical identity and expression). We also examined their phenotypic associations, as well as genetic and environmental overlap with general personality traits, including the Big Five and Trait Empathy facets. Additive genetic and unique environmental effects largely accounted for the variation in the four dimensions (heritability 38%−52%, mean = 45%), though univariate analyses of the social bonding dimension indicated common environmental influences for this specific subscale. In line with previous studies, trait-congruent phenotypic associations were found between specific personality traits and music use motives, including facets of negative emotionality and musical emotion regulation. Other facets – particularly aesthetic sensitivity (open-mindedness) and fantasy (trait empathy) – were closely tied to all dimensions. Multivariate biometric modeling of the links between personality traits and motivations for music use revealed that these relationships were primarily driven by correlated genetic factors, with personality traits accounting for 40%−66% of the total genetic variance and 5%−17% of the total environmental variance in the music use motivation dimensions. These findings shed new light on the etiology of dispositional music use and provide a comprehensive baseline for future investigations of associations with personality, mental health, and well-being.